2015
DOI: 10.1016/j.cardfail.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota-Dependent Phosphatidylcholine Metabolites, Diastolic Dysfunction, and Adverse Clinical Outcomes in Chronic Systolic Heart Failure

Abstract: Background Trimethylamine-N-oxide (TMAO) has been linked to increased cardiovascular risk. We aim to determine the prognostic value of TMAO and its dietary precursors, choline and betaine, in heart failure (HF). Methods and Results In 112 patients with chronic systolic HF with comprehensive echocardiographic evaluation, we measured plasma TMAO, choline, and betaine by mass spectrometry. Median TMAO levels, choline, and betaine levels were 5.8 [3.6, 12.1] μM, 10.9 [8.4, 14.0] μM, 43.8 [37.1, 53.0] μM, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
228
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(264 citation statements)
references
References 21 publications
16
228
2
2
Order By: Relevance
“…When comparing with reported TMAO concentrations, healthy control participants showed similar median values to previous healthy cohorts [2,6]. Patients suffering from SHF reported elevated levels to other HF cohorts [2,3], but similar to those suffering from chronic kidney disease [6]. This result, although interesting, is derived from a limited patient population but demonstrates the clinical applicability of the described method.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…When comparing with reported TMAO concentrations, healthy control participants showed similar median values to previous healthy cohorts [2,6]. Patients suffering from SHF reported elevated levels to other HF cohorts [2,3], but similar to those suffering from chronic kidney disease [6]. This result, although interesting, is derived from a limited patient population but demonstrates the clinical applicability of the described method.…”
Section: Discussionsupporting
confidence: 71%
“…To our knowledge, we describe the first example of a clinical assay utilising a Synapt generation ToF-MRM assay for a compound that can provide clinical prognostic value to a variety of diseases [1][2][3]25]. The assay is linear over nearly 3 orders of magnitude, has a limit of detection of 0.05 µmol\L and has a total injection-to-injection run time of 3 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, gut microbes were shown to play an obligatory role in trimethylamine N-oxide (TMAO) formation upon processing of common dietary components (e.g., choline in egg yolk or Lcarnitine in meat) both in mice 4,5 and in humans. [6][7][8][9] These studies also demonstrated that TMAO was not merely a biomarker, but it was also a mediator of alterations in cholesterol and sterol metabolism and can directly enhance atherogenesis. 4,5 Pathophysiologically, TMAO may also interact with other host neurohormonal systems, as observed in a rat model whereby angiotensin II infusion in the setting of elevated TMAO levels led to sustained augmentation of BP.…”
mentioning
confidence: 90%
“…Several studies have reported an association between plasma TMAO and choline levels in patients with heart failure [9][10][11][12]. TMAO negatively regulates glucose metabolism which leads to diabetes mellitus [13].…”
mentioning
confidence: 99%